Revolutionary Committees in Siberia during the Civil War: National Historiography - Kurenkov, A. V. (Вестник Кемеровского государственного университета, 2022)
This article reviews domestic approaches to the issue of the revolutionary committees in Siberia during the Civil War, e.g., their genesis, development, status, structure, forms, methods, activities, social and party composition, interaction with each other and the Russian Communist Party, the transfer of power to the Soviets and Executive Committee, etc. Soviet historians were unanimous in their positive assessment of the revolutionary committees as the organs of proletariat dictatorship that waged a relentless struggle against class enemies and defended the revolutionary progress. However, this approach resulted from the rigid ideological guidelines of the Soviet period. The collapse of the communist ideology liberated the domestic historical science from the comprehensive control of the Party and state organs. Post-Soviet historians expanded the range of methodological approaches and principles, which allowed them to take a new perspective of the Siberian revolutionary committees. They were able to clarify the motives behind the revolutionary committees, determine their place in the system of Bolshevik power, identify their relationship with higher Party and Soviet structures, reveal the level of education and qualifications of their leaders and members, etc. The topic of the Siberian revolutionary committees has received enough scientific attention. However, some gaps still remain, e.g., staff structure, the exact mechanism of their interaction with the Party, their influence on the political, social, economic, and cultural development of Siberia, etc.